2016
DOI: 10.1097/rlu.0000000000001176
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Metastatic Prostate Carcinoma Shown by 68Ga-PSMA PET/CT

Abstract: We present the F-FDG and Ga prostate-specific membrane antigen PET/CT images of a 61-year-old patient with a newly diagnosed prostate carcinoma (4 + 4 Gleason score) and high serum prostate-specific antigen levels (460 ng/mL). In F-FDG PET/CT, minimal uptake was demonstrated in the prostatic mass without any accompanying pathological uptake. However, Ga prostate-specific membrane antigen PET/CT revealed multiple pathological uptake in the lung nodules, mediastinal nodes, abdominal-pelvic lymph nodes, bone lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…After the full texts of potentially eligible studies were read, 45 papers were included. An overview of the 37 included papers is shown in Table 1 (31 case series) and Table 2, in which six single cases are presented (Chakraborty et al, 2015b;Lawal et al, 2015;Uprimny et al, 2015;Agarwal et al, 2016;Sasikumar et al, 2016;Soydal et al, 2016). Finally, one radiochemistry study was excluded because it reported data from a single patient using 68 Ga-PSMA-11 versus 68 Ga-CHX-A"-DPTA-PSMA PET/CT, an uncommon PET ligand (Wustemann et al, 2016).…”
Section: Characteristics Of the Included Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…After the full texts of potentially eligible studies were read, 45 papers were included. An overview of the 37 included papers is shown in Table 1 (31 case series) and Table 2, in which six single cases are presented (Chakraborty et al, 2015b;Lawal et al, 2015;Uprimny et al, 2015;Agarwal et al, 2016;Sasikumar et al, 2016;Soydal et al, 2016). Finally, one radiochemistry study was excluded because it reported data from a single patient using 68 Ga-PSMA-11 versus 68 Ga-CHX-A"-DPTA-PSMA PET/CT, an uncommon PET ligand (Wustemann et al, 2016).…”
Section: Characteristics Of the Included Papersmentioning
confidence: 99%
“…Finally, one radiochemistry study was excluded because it reported data from a single patient using 68 Ga-PSMA-11 versus 68 Ga-CHX-A"-DPTA-PSMA PET/CT, an uncommon PET ligand (Wustemann et al, 2016). An overview of the 37 included papers is shown in Table 1 (31 case series) and Table 2, in which six single cases are presented (Chakraborty et al, 2015b;Lawal et al, 2015;Uprimny et al, 2015;Agarwal et al, 2016;Sasikumar et al, 2016;Soydal et al, 2016). Most of the studies included patients with biochemical recurrence, but some studies included data on staging, whereas, other studies used populations with different stages of prostate cancer.…”
Section: Characteristics Of the Included Papersmentioning
confidence: 99%
“…Citations excluded in screening are held in a Covidence database by the authors and can be made available if required. Articles excluded by quality review are listed in the supplementary materials [55][56][57][58][59].…”
Section: Data Availabilitymentioning
confidence: 99%
“…), and high specific uptake in PSMA-expressing tissues and tumor (tumor uptake 7.7 ± 1.5 % IA/g at 1 h p.i.). The ability to image PSMA using 68 Ga-HBED-CC-PSMA showed great promise not only preclinically but also clinically [ 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. The dimerization of the same pharmacophore, Lys-Urea-Glu, coupled to the same spacer Ahx, through the chelator HBED-CC (PSMA-10) (compound 40 , Figure 11 ) was also published by Schäfer et al [ 130 ].…”
Section: Urea-based Psma Inhibitorsmentioning
confidence: 99%
“…68 Ga-PSMA-11 PET-CT imaging was firstly introduced in 2013 by Afshar-Oromieh et al in 37 patients with relapsing prostate cancer ( Figure 19 ) [ 107 , 145 ]. Within a relatively short time frame, 68 Ga-PSMA-11 has been thoroughly clinically assessed by several research groups, indicative of the large number of publications the last four years [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. Although the background uptake of 68 Ga-PSMA-11 in salivary and lacrimal glands was abnormally high, PET-CT imaging was obtained leading to excellent detection of the metastatic lesions of prostate cancer.…”
Section: Clinical Assessment Of Radiolabeled Psma Inhibitors: Currmentioning
confidence: 99%